Mexico : Paving the Way for the Development of Emissions Trading - Partnership for Market Readiness (World Bank, Washington, DC, 2021)
Mexico has made great strides recently in its fight against climate change. The enactment of the Climate Change Law in 2012 and its reform in 2018 led to the creation of a series of administrative and policy instruments to guide domestic action on climate mitigation and adaptation. The development and implementation of this agenda created new and different challenges involving the design and adoption of new fiscal, economic, and market-based instruments. Mexico opted for the development of an Emission Trading Scheme (ETS) as its main instrument to scale up climate change mitigation efforts. To address design and implementation challenges, the country sought avenues of international cooperation and technical assistance, including by joining the Partnership for Market Readiness (PMR). Established and managed by the World Bank, the PMR is a grant-based, global partnership that provides systemic support and funding for technical and institutional capacity development and piloting of new and innovative market-based instruments. This report presents the main activities undertaken under the project and identifies the main outcomes. Observed results confirm the important contribution of this project to the Mexican development and climate policy landscape, developing technical knowledge products, practical tools and capacity building activities that are shaping the design of the national carbon pricing policy mix and informed the review of the NDC (submitted to the UNFCCC in December 2020). The report is organized as follows: section two outlines the country context prior to the PMR project; section three outlines the project goals; the implementation process and the key outcomes; and final sections evaluate the impacts of the project in the country and outlines next steps, lessons learned, and recommendations.